Investigating Employees’ Tenure and Performance among Middle Managers: The Moderating Role of Psychological Empowerment - Santhi Raghavan; Sanjeev Janardhanan (2019)
This study aims to analyses the influence of one important demographic variable, employees’ tenure at their organizations towards improving and enhancing employee performance among supervisory level staff in the ceramic tile manufacturing industry. Based on the literature discussed, the role of psychological empowerment will also be studied to see if it has any moderating influence on the relationship between employee’s tenure and their performance. Using the quantitative method, the population for this study was 239. The primary data was gathered in the form of questionnaires with a Likert-type scale which was then analyzed using multiple regression methods. The results of the study have shown that employees’ tenure has an influence on their performance but in the presence of psychological empowerment, tenure does not improve performance. (Abstract by authors)